Validity and Reliability of Asbestos Knowledge and Awareness Questionnaire for Environmental Asbestos Exposure in Rural Areas - Selma Metintaş (Eurasian Journal of Pulmonology, 2017)
Objective: There is no treatment for asbestos–related diseases, but they can be prevented. One of the first interventions is to improve the knowledge level of people in order to protect people from asbestos and asbestos–related diseases. The present study was conducted to develop a questionnaire for measuring the knowledge and awareness level of asbestos and also assess its validity and reliability in a rural population that is exposed to asbestos environmentally.